A preliminary microarray assay of the miRNA expression signatures in buccal mucosa of oral submucous fibrosis patients. (15th March 2016) - Chickooree, Daminee; Zhu, Keke; Ram, Vahsish; Wu, Han Jiang; He, Zhi Jing; Zhang, Sheng
Abstract : Objectives: The objectives of this study are threefold: First is to perform a preliminary microarray analysis of miRNA expression profile to filter out differentially expressed miRNA in oral submucous fibrosis, second is to perform a bioinformatics analysis to identify miRNA‐specific predicted genes, and third to retrieve those miRNAs from literature and account for the findings of our investigations. Methods: Buccal mucosa samples from three clinically evident OSF patients and three normal volunteers were collected. Agilent Human miRNA microarray experiments were carried out to analyze the miRNA expression profile in both OSF and normal tissues. To identify molecular pathways potentially altered by expression of miRNAs, DAVID software was used. This application performs an enrichment analysis of multiple miRNA target genes comparing each set of miRNA targets to known KEGG pathway. Results: A total of 11 unique miRNAs were differentially expressed. The overexpressed miRNAs were hsa‐miR‐455‐3p, hsa‐miR‐455‐5p, and hsa‐miR‐623, and underexpressed miRNAs were hsa‐miR‐1290, hsa‐miR‐3180‐3p, hsa‐miR‐4792, hsa‐miR‐509‐3‐5p, hsa‐miR‐5189, hsa‐miR‐610, hsa‐miR‐760, and hsa‐miR‐921. Six miRNAs namely miR‐455, miR‐760, miR‐623, miR‐610 and miR‐509‐3‐5p were selected. Conclusion: This study shows that miRNA chip can be used for high‐throughput screening of miRNA. Target prediction and annotation of the miRNAs demonstrated that the binding, metabolic process, molecular, and cellular process are the most common functions of the predicted targets of these newly identified miRNAs.